2020
DOI: 10.1016/j.xfre.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of class III obesity on outcomes and complications of transvaginal ultrasound-guided oocyte pickup

Abstract: Objective: To assess the impact of class III obesity on outcomes and complications of transvaginal ultrasound-guided oocyte pickup (OPU). Design: Retrospective cohort study. Setting: Hospital-based fertility clinic. Patient(s): All women undergoing OPU procedures during autologous in vitro fertilization (IVF) and oocyte banking cycles, grouped by patient body mass index (BMI: <25, 25-29.9, 30-34.9, 35-39.9, R40 kg/m 2). Intervention(s): Transvaginal OPU under conscious sedation. Main Outcome Measure(s): Sedati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recent studies reported additional concerns regarding OPU for severely obese women (BMI >40 kg/m 2 ), including anesthetic-related risks and technical difficulties such as an inability to access the ovaries [ 4 , 35 ]. In this article, BMI was not associated with an increased frequency of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported additional concerns regarding OPU for severely obese women (BMI >40 kg/m 2 ), including anesthetic-related risks and technical difficulties such as an inability to access the ovaries [ 4 , 35 ]. In this article, BMI was not associated with an increased frequency of complications.…”
Section: Discussionmentioning
confidence: 99%